Evaluation of transfer factors of 226Ra, 232Th, and 40K radionuclides from soil to grass and mango in the northern region of Bangladesh - Siraz, M. M. Mahfuz; Das, S. K.; Mondol, M. S.; Alam, M. S.; Mahmud, Jubair Al; Rashid, Md. Bazlar; Khandaker, Mayeen Uddin *; Yeasmin, S. (Springer, 2023)
Bangladesh is a rapidly developing country, which is vulnerable to various types of pollution due to the large-scale industrial and associated human activities that might potentially affect the locally harvested foodstuffs. Therefore, the transfer factor is an essential tool to assess the safety of foodstuffs due to the presence of natural radioactivity in environmental matrix and/or strata. This is a first study of its kind conducted in a well-known region for mango farming in Bangladesh, measuring the uptake of naturally occurring radioactive materials (NORMs) by grass and mango from soil to assess the ingestion doses to humans. The HPGe gamma-ray detector was used to determine the concentrations of NORMs in samples of soil (20), grass (10), and mango (10), which were then used to calculate the transfer factors of soil to grass and soil to mango. Average activity concentrations of 226Ra, 232Th, and 40K in associated soil samples (47.27 ± 4.10, 64.49 ± 4.32, 421.60 ± 28.85) of mango and 226Ra and 232Th in associated soil samples (45.07 ± 3.93, 52.17 ± 3.95) of grass were found to exceed the world average values. The average transfer factors (TFs) for mango were obtained in the order of 40K(0.80) > 226Ra (0.61) > 232Th (0.31), and for grass, it shows the order of 40K (0.78) > 232Th (0.64) > 226Ra (0.56). However, a few values (3 mango samples and 3 grass samples) of the estimated TFs exceeded the recommended limits. Moreover, Bangladesh lacks the transfer factors for most of the food crops; therefore, calculation of TFs in the major agricultural products is required all over Bangladesh, especially the foodstuffs produced near the Rooppur Nuclear Power Plant, which is scheduled to be commissioned in 2023.